Solanum fernandesii (Solanaceae): A new species of ‘spiny solanum’ of the Gardneri clade from northeastern Brazil - Sampaio, Valéria Da Silva; Moura, Ricardo Loyola De; Loiola, Maria Iracema Bezerra (Phytotaxa, 2016)
A new spiny species of Solanum L., member of the Gardneri clade, is described from northeastern Brazil. Solanum fernandesii is found in open disturbed areas of coastal plains (tabuleiros) in the caatinga biome of the states of Alagoas, Bahia, and Ceará, from sea level to 900 m of altitude. It is morphologically similar to S. agrarium Sendtn., a neotropical species known from hot and dry areas of Colombia, Venezuela, the Caribbean, and central-eastern Brazil. The two species differ mainly in their habit, blade margins, shape of the calyx in fruit, and seeds. The new species is here described and illustrated. According to IUCN, Solanum fernandesii should be regarded as Least Concern (LC).